Effects of kefir fractions on innate immunity - Vinderola, Celso Gabriel (2006)
Innate immunity that protects against pathogens in the tissues and circulation is the first line of defense in the immune reaction, where macrophages have a critical role in directing the fate of the infection. We recently demonstrated that kefir modulates the immune response in mice, increasing the number of IgA + cells in the intestinal and bronchial mucosa and the phagocytic activity of peritoneal and pulmonary macrophages. The aim of this study was to further characterize the immunomodulating capacity of the two fractions of kefir (F1: Solids including bacteria and F2: Liquid supernatant), by studying the cytokines produced by cells from the innate immune system: Peritoneal macrophages and the adherent cells from Peyer's patches. BALB/c mice were fed either kefir solid fraction (F1) or kefir supernatant (F2) for 2, 5 or 7 consecutive days. The number of cytokine (IL-1α, IFNγ, TNFα, IL-6 and IL-10) producing cells was determined on peritoneal macrophages and adherent cells from Peyer's patches. Both kefir fractions (F1 and F2) induced similar cytokine profiles on peritoneal macrophages (only TNFα and IL-6 were up-regulated). All cytokines studied on adherent cells from Peyer's patches were enhanced after F1 and F2 feeding, except for IFNγ after F2 administration. Moreover, the percentage of IL-10 + cells induced by fraction F2 on adherent cells from Peyer's patches was significantly higher than the one induced by fraction F1. Different components of kefir have an in vivo role as oral biotherapeutic substances capable of stimulating immune cells of the innate immune system, to down-regulate the Th2 immune phenotype or to promote cell-mediated immune responses against tumours and also against intracellular pathogenic infections.